2012
DOI: 10.1007/s10565-011-9207-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of ErbB2 mediated AKT and MAPK pathway in gall bladder cell proliferation induced by argemone oil and butter yellow

Abstract: The effect of noncytotoxic doses of argemone oil (AO) and butter yellow (BY), the common adulterants in edible oil, on free radical generation and signaling pathway for cell proliferation in primary cells of gall bladder (GB) was undertaken. AO and BY showed no cytotoxicity at 0.1 μl/ml and 0.1 μg/ml concentration, respectively. AO caused significant increase in ROS after 30 min and RNS after 24 h in GB cells while no change was observed following BY treatment. Enhanced level of COX-2 was observed following AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Other strong performers for sustained proliferation were BPA (activated all targets activated by the insecticides and fungicides above except growth factors and their receptors, B lymphocyte markers and PPAR, but included cell cycle regulators alongside AP-1 proteins/transcription/translation regulators and downstream signaling) ( 272 , 276 , 278 , 279 ) (also identified in ToxCast high-throughput assay, 2009), polyfluorinated octinoid sulfate and polybrominated diphenylethers (flame retardants) that either activated AhR ( 280 , 281 ) or up to five other targets that included steroid receptors, growth factors, cytokines and cell cycle regulators ( 109 ) (ToxCast high-throughput assay 2009). Three other contenders were phthalates (plasticizers that acted via three targets that included AhR, steroid hormone receptors and PPAR) ( 282–285 ), trenbolone acetate (a synthetic anabolic steroid that unsurprisingly acted through steroid hormone receptors) ( 120 , 286–290 ) and finally, edible oil adulterants (food contaminants produced during food processing that acted via downstream signaling) ( 291 , 292 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other strong performers for sustained proliferation were BPA (activated all targets activated by the insecticides and fungicides above except growth factors and their receptors, B lymphocyte markers and PPAR, but included cell cycle regulators alongside AP-1 proteins/transcription/translation regulators and downstream signaling) ( 272 , 276 , 278 , 279 ) (also identified in ToxCast high-throughput assay, 2009), polyfluorinated octinoid sulfate and polybrominated diphenylethers (flame retardants) that either activated AhR ( 280 , 281 ) or up to five other targets that included steroid receptors, growth factors, cytokines and cell cycle regulators ( 109 ) (ToxCast high-throughput assay 2009). Three other contenders were phthalates (plasticizers that acted via three targets that included AhR, steroid hormone receptors and PPAR) ( 282–285 ), trenbolone acetate (a synthetic anabolic steroid that unsurprisingly acted through steroid hormone receptors) ( 120 , 286–290 ) and finally, edible oil adulterants (food contaminants produced during food processing that acted via downstream signaling) ( 291 , 292 ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we sought to determine how GTSE1 exerted these biological effects by characterizing its effect on known functional molecule and signaling pathways. Accumulated reports have shown that the PI3K/AKT and ERK/MAPK are the signaling pathways for tumor growth and invasion (Mishra et al 2012 ; Sui et al 2015 ). Therefore, we assessed the effect of GTSE1 on the levels of phosphorylation of AKT and ERK.…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies found that ROS can promote cell proliferation at low concentration. EGF is an essential growth factor for epithelial cell proliferation by inducing intracellular ROS production . EGF-induced ROS generation is associated with activation of Akt and mitogen-activated protein kinases (MAPK) signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic effects of the cyadox and its metabolites on L02 cells were evaluated by MTT and LDH leakage assay. For MTT assay, cells were cultured in 96-well cell plates (1 × 10 5 cells/mL) treated with different concentration of cyadox, cy1, cy4, cy6, cy12 (20,40,80,160, and 200 μM), for 12, 24, and 48 h, respectively. After incubation, the cells were treated with 100 mL/ well with MTT solution (0.5 mg/mL) for 4 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%